ANALISIS PENGGUNAAN MEDIA SOSIAL FACEBOOK DALAM PERKEMBANGAN UMKM GULO PUAN DI DESA BANGSAL KECAMATAN PAMPANGAN - Anggi Julianti; Fadilla Fadilla; Moh. Faizal (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
Small Microcus Business (UMKM) is a small business activity but is able to provide a major effect for the economy in Indonesia. That is to expand employment, play a role in the process of equity and increase in community revenue, and encourage the realization of national stability. But to realize it is necessary to be able to compete globally, by utilizing technological developments at this time not to be left behind with the development of the age. Utilization of social media especially Facebook as a promotional tool to make it easy for marketing UMKM Gulo Puan in the village of Bangsal District of District Objective is one of the strategies that are currently used. With easy access, wide tissues, fast working methods and also costs that will be able to provide positive and profitable impacts for MSME. The results of this study show that the use and use of social media as a promotional tool can increase the competitiveness of UMKM-UMKM Gulo Puan in the village of Bangsal District District in January aspects of increased sales than compared to using social media. But when revisited still many non-MSMEs that have not used and utilize social media for marketing online caused by various things.